An Efficient Smart Restaurant Assistance for Customizing the Performance using Facial Recognition - B. Naresh Kumar Reddy (International Journal of Control and Automation, 2020)
Artificial intelligence is one of the most trending technology which is user-friendly for our day to day life. There is a rapid growth in the economic and industrial areas. Due to excessive human load and hardware implementation for executive tasks in our daily environment results in low performance, time delays, lack of customization. In order to solve all these issues and provide an ease environment in the crowed places such as restaurants, we proposed an algorithm which acts as a smart assistance for the users. This smart assistance provides the order data to the customer either by displaying it on the Smart LED screen or through the voice assisting the customer based on specific parameters. The experimental outcomes of this approach outperforms with the other automated techniques by providing an ease environment to all kinds of people, high performance, more productivity in a customized format.